Upper limb III, Elbow joint & cubital fossa - Hillen, Berend; Groen, Gerbrand J. (Amsterdam : Elservier Science, 1998)
(Producer) An atlas of continuous cross-sections. Offers over 9,000 images of normal anatomy and 1,200 correlative images from CT, MRI, and histology.
CD is available at Koleksi Media, Perpustakaan HUKM
Also contains version issued on CD-I disc
System requirements: IBM-compatible computer with an 80386-33 MHz 486 processor or higher; 4 Mb or more RAM, 3.5 Mb free hard disc space; Microsoft Windows 3.1, 3.11 or Windows 95 or 98 installed; mouse; VGA graphics adaptor supporting 256 colours (at VGA 640x480 or SVGA 800x600 resolution); CD-ROM drive accessible from Microsoft Windows (a double-speed drive is highly recommended).
System requirements: CD-i player upgraded with digital video (DV) cartridge
Keywords: Elbow Joint -- anatomy & histology -- atlases -- CD-ROM